Supporting the Increase in Productivity and Marketing of Chicken Floss to Enhance the Competitiveness of Dapur Hoki's Home Industry - Deviana, Deviana; Rudita, I Made; Yudana, I Gusti Putu Hardi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The chicken floss production business of Dapur Hoki has garnered significant interest, yet faces challenges in production, marketing, and financial management. To address these issues, support was provided in the form of production equipment aimed at boosting partner sales revenue, creating packaging labels for partner identity, leveraging social media to expand marketing reach, and assisting in bookkeeping to clarify capital and profit from chicken floss sales. The data acquisition uses both qualitative and quantitative methods. Qualitative data is obtained through interviews, while quantitative data is collected through the distribution of questionnaires. Evaluation results using a questionnaire among partners yielded an average score of 95%, indicating the service outcomes were rated as Excellent. Furthermore, the bookkeeping support enabled partners to effectively calculate their capital and profits from their business operations.